2019
DOI: 10.3390/foods8100464
|View full text |Cite
|
Sign up to set email alerts
|

Food Purchasing Behaviors of a Remote and Rural Adult Solomon Islander Population

Abstract: The aim of this study was to investigate the food purchasing behaviors of an adult Solomon Islander population within a transitioning food system in Auki, Malaita. Food purchasing behavior measures included; venue type and transportation for purchasing food, previous day expenditure on food purchases, number of weekly shopping experiences for store foods (generally long-life shelf and frozen items) and fresh foods (such as fruits and vegetables and fresh fish) and the importance of factors (i.e., price) on pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(48 reference statements)
1
3
2
Order By: Relevance
“…A study in Fiji also showed a similar trend for a rural population engaging in farming (O'Meara et al 2019). All age groups interviewed in this study frequently bought food from the store and markets, corresponding to findings in Bottcher et al (2019).…”
Section: Farmers' Social-demographic Profilessupporting
confidence: 78%
See 1 more Smart Citation
“…A study in Fiji also showed a similar trend for a rural population engaging in farming (O'Meara et al 2019). All age groups interviewed in this study frequently bought food from the store and markets, corresponding to findings in Bottcher et al (2019).…”
Section: Farmers' Social-demographic Profilessupporting
confidence: 78%
“…According to Bottcher et al (2019), Horsey et al (2019) and SINSO, SIMoHMS, and PC (2017), about 20.0% of the Malaita population has never received any form of formal education. This study found a corresponding figure, with 18.0% of the farmers (14.0% female and 4.0% males) having received no formal education.…”
Section: Farmers' Social-demographic Profilesmentioning
confidence: 99%
“…There is also high purchase power in zone 2 compared to zone 1. However, while the study revealed high purchasing power for zone 2 households than zone 1, it is lower than the purchasing power of the Auki (main town area in Malaita Island) population, whose food items were primarily obtain from the Auki market and the shops, as reported in a previous study [41].…”
Section: Household Dietary Pattern: Accessibility and Availabilitycontrasting
confidence: 43%
“…While several food items can be sourced locally, that is, fish, fruits and vegetables, there was concern about increased access and availability of highly processed, imported foods; however, we did not explore if this based on physical and/or economic accessibility. Evidence shows that physical availability of these highly processed foods has increased throughout some PICT in recent years (1,2,6,43,44) . Stakeholders discussed these foods in reference to convenience; however, we did not explore what this convenience looks like, that is, convenient access to or convenient for consumption.…”
Section: Discussionmentioning
confidence: 99%